Penerapan Algoritma Crawling dalam Otomatisasi Verifikasi Pembayaran Tiket Seminar - Eldy Dwi Sentosa; Iskandar Fitri; Agus Iskandar (STMIK Budi Darma, 2021)
The system for viewing student seminar payment data can be viewed through administrator controls. The seminar payment confirmation process for National University students still uses the manual system by paying the seminar organizer so it takes longer to process the seminar payment. The purpose of creating this system is to speed up the payment time of the seminar. This system uses a unique 3-digit code in each payment of seminar participants, this unique 3-digit code acts as a mark that differentiates student payments so that it does not require confirmation to the seminar organizer. Cron work will be performed on UNIX-based operating systems (Linux, Ubuntu, etc.) which function to perform tasks or scripts automatically. The content of the script is an order to execute the payment confirmation order against the participant. This level of research consists of several stages, namely needs analysis, design, writing system application code, application testing. This investigation has resulted in an application that can expedite the payment verification process by matching the number of transfer participants with those in the database. The results of testing the payment verification process are influenced by the Crawl Algorithm to help the payment process become more effective. With results that have been tested on average, it shows 4.8 seconds to confirm the participant's payment. With this seminar payment system, you can save time to process seminar payments.